Ensiling Grape Pomace With and Without Addition of a Lactiplantibacillus plantarum Strain: Effect on Polyphenols and Microbiological Characteristics, in vitro Nutrient Apparent Digestibility, and Gas Emission - De Bellis, Palmira; Maggiolino, Aristide; Albano, Clara; De Palo, Pasquale; Blando, Federica (Frontiers in Veterinary Science, 2022)
The present study investigated the effects of different grape pomace storage techniques on the effectiveness as feed on in vitro ruminant digestion efficiency. Grape pomace from an autochthonous red grape variety (cv Nero di Troia) was used as fresh (GP) or ensiled, both without additives (SIL) and with the addition of a bacterial strain, Lactiplantibacillus plantarum 5BG (SIL+). All the different storage treatments were subject to chemical and microbiological evaluation, as well as in vitro digestibility, and gas production. Microbiological data revealed the good quality of grape pomace and silages due to the lactic acid bacteria populations and low presence, or absence, of undesirable microorganisms. The addition of L. plantarum 5BG influenced the chemical characteristics of the silage (SIL+). Ensiling technique deeply changed the polyphenolic composition, reducing anthocyanins, flavonols and flavanols (condensed tannins precursors), particularly when L. plantarum 5BG was added. Antioxidant capacity was reduced by ensiling, in correlation with the polyphenolic content decrease. The oxygen radical absorbance capacity (ORAC) value of SIL+ was the lowest (P < 0.01) and its total phenol content was lower than SIL (P < 0.01). No statistical differences were observed between GP, SIL and SIL+ on the antioxidant capacity by TEAC assay (P > 0.05). Ensiling did not affect the grape pomace nutrient profile, except for the reduction in NFC content. Apparent in vitro digestibility showed how ensiling increased dry matter (DM), organic matter (OM), neutral detergent fibre (NDF), crude protein (CP), ether extract (EE) and non-fibre carbohydrates (NFC) disappearance (P < 0.01), particularly with the L. plantarum 5BG inoculation. Moreover, SIL+ showed the lowest propionic acid (P < 0.05) and the highest methane (P < 0.01), butyric acid (P < 0.01) and nitrogen (P < 0.05) in vitro production. Ensiling GP resulted in a better in vitro digestibility, particularly if L. plantarum 5BG strain is added, probably due to the reduction of flavanols and their lower microbial activity inhibition.